Estudio de prefactibilidad para la instalación de una planta de joyería de plata sostenible y aromática de inspiración precolombina - Burgos, Agustina Micaela (2023)
This project presents a pre-feasibility study for the installation of a jewelry plant based on the circular economy, whose designs sought to praise pre-Columbian Peruvian cultures. These jewels were designed to contain within them a fabric filter impregnated with essential oil of molle, sacred tree of the Incas. The scientific method was used to test the hypothesis that the project is technically, socially and economically feasible. A target market of adults between 21 and 59 years of age from NSE A and B seeking to consume in a culturally and environmentally responsible manner was defined, with a maximum specific demand of 3908 pieces of jewelry. The plant was located in the industrial district of Centro, in Metropolitan Lima, where indirect 3D printing combined with the lost wax method was chosen for the manufacture of jewelry, and steam extraction was chosen for the molle essential oil. The plant capacity allows for the production of 4085 pieces of jewelry annually. Finally, the project was found to be profitable thanks to an economic and financial evaluation that yielded an IRR greater than the COK, a positive NPV and a short payback period.